Correlative nanoscopy: A multimodal approach to molecular resolution. Issue 10 (6th May 2021) - Jadavi, Samira; Bianchini, Paolo; Cavalleri, Ornella; Dante, Silvia; Canale, Claudio; Diaspro, Alberto
Abstract: Atomic force microscopy (AFM) is a nano‐mechanical tool uniquely suited for biological studies at the molecular scale. AFM operation is based on mechanical interaction between the tip and the sample, a mechanism of contrast capable of measuring different information, including surface topography, mechanical, and electrical properties. However, the lack of specificity highlights the need to integrate AFM data with other techniques providing compositional hints. In particular, optical microscopes based on fluorescence as a mechanism of contrast can access the local distribution of specific molecular species. The coupling between AFM and super‐resolved fluorescence microscopy solves the resolution mismatch between AFM and conventional fluorescence optical microscopy. Recent advances showed that also the inherently label‐free imaging capabilities of the AFM are fundamental to complement the fluorescence images. In this review, we have presented a brief historical view on correlative microscopy, and, finally, we have summarized the progress of correlative AFM‐super‐resolution microscopy in biological research. Abstract : Correlative nanoscopy is a new field of application that implies integrating two or more microscopy techniques able to provide resolution at the nanoscale. In particular, in the last years, the coupling between the atomic force microscope (AFM) and optical super‐resolution microscopes gives rise to a new tool with the unique capability to investigate living/dynamic biological systems. Here, we presented the fundamental step in the development of this new technique. We decided to start from the origin of the correlative AFM‐optical microscopy, giving a historical overview on that, in our mind, could be helpful, especially for young researchers, to understand the needs that drive the efforts spent toward the development of optical nanoscopy.